Advanced exergy-based methods used to understand and improve energy-conversion systems. (15th February 2019) - Morosuk, Tatiana; Tsatsaronis, George
Abstract: Exergy-based methods are powerful tools for developing, evaluating, understanding, and improving energy conversion systems. This paper deals with integrated advanced exergy-based evaluations. In addition to conventional methods, advanced exergy-based analyses consider (a) the interactions among components of the overall system, and (b) the real potential for improving each important system component. The main role of an advanced analysis is to provide energy conversion system designers and operators with information useful for improving the design and operation of such systems. Splitting the exergy destruction, the capital investment cost, and the component-related environmental impact associated with each single component of an energy conversion system into endogenous/exogenous and avoidable/unavoidable parts and using a further splitting of the exogenous exergy destruction improves (a) our understanding of the processes that take place, and (b) the quality of the conclusions for improvement obtained from the analysis. This paper discusses the main features and some recent developments in the area of advanced exergy-based methods. Application of the method to a simple air refrigeration machine confirms the correctness of the approach.